From Electocracy to Democracy: Coalition, Cohesion, and Function - Talib, Kartini (Politeia: Jurnal Ilmu Politik, 2020)
Generally, democracy composes the elements of election, rights and liberty, middle class, and the rules of law to govern the state and people. Malaysia had limited experience of a democracy that was absent from the elements above. It had its first election during the colonial era that dictates the function of an election. Later, the election becomes routine every five years that makes it an electocracy or a political culture lacks political literacy. The post-independence context of a strong leader and a dominant party alliance to rule the state and society resulted in making political analysts criticizing Malaysia as a state of the quasi, semi, and syncretic democracy. The recent power transition with no record of violence in Fourteen General Election (2018) proves that the previous label of democracy in Malaysia is obsolete. Therefore, the analysis tool of assessing Malaysian politics is still dormant with the Western perspective of the two-party system, the end of racial politics hence assuming the beginning of an ideology-based party and the belief that the new Malaysia will fit in the western mold of democracy. The robust information technology via social media harvesting new challenges for democracy in Malaysia. It cannot escape the spread of fake news or disinformation to influence voters. The game of fake news has put Malaysia as a state of electocracy full of unskilled politicians to govern the multiethnic nation.